Pengaruh Implementasi Economic Order Quantity dan Digitalisasi terhadap Profitabilitas Usaha Mikro, Kecil dan Menengah di Kota Bekasi - Muhammad Muhammad; Nurul Kamila; Huda Aulia Rahman; Zalzabilla Putri Ekawati (LPMP Imperium, 2026)
This study intends to analyze the influence of the implementation of Economic Order Quantity (EOQ) and digitalization on the profitability of Micro, Small, and Medium Enterprises (MSMEs) in Bekasi City. The low efficiency of inventory management and the limited use of digital technology are still obstacles for MSMEs. A quantitative approach was used by involving 32 MSMEs selected through purposive sampling from a population of 418 MSMEs. Primary data were analyzed using multiple linear regression assisted by SPSS tools, accompanied by validity, reliability, and classical assumptions tests to ensure the feasibility of the model. The results of the study show that the EOQ variable has no effect on profitability. This shows that MSMEs have not been able to implement the EOQ method optimally. On the contrary, digitalization affects profitability significantly and positively. Simultaneously, EOQ and digitalization also affect profitability significantly. The determination coefficient reveals that 76% of the variation in profitability is illustrated by the implementation of Economic Order Quantity (EOQ) and digitalization. Public interest statementsThis study helps MSMEs in understanding the basics of inventory management and reminds that digitalization is a necessity to improve business performance and competitiveness.